Synergistic Effects of NiO, Fe3O4, and WO3 Bilayers With Spiro-OMeTAD in CsFAMA Perovskite Solar Cells - Muhammad Anwar Jan; Akbar Ali Qureshi; M. Umair Ahsan; Hafiz Muhammad Noman; Muhammad Adnan; Arooma Khalid (Advances in Materials Science and Engineering)
The selection of appropriate materials for each layer in the device design has a significant impact on the photovoltaic (PV) performance of perovskite solar cells (PSCs). In particular, the hole transport layer (HTL) is responsible for extracting holes from the perovskite layer and transferring them to the relevant electrode. In this work, we investigated the impact of various commercially available dispersions of metal oxide (MOX) hole transport materials (HTMs) including nickel oxide (NiO), iron oxide (Fe3O4), tungsten oxide (WO3), and Spiro-OMeTAD (as a reference) in a single and bilayer architecture on the PV performance of PSCs. The comparative analysis reveals that the NiO/Spiro combination delivers the best overall performance, achieving a power conversion efficiency (PCE) of 18.21% under optimized conditions. In spite of offering an effective charge extraction, the optimal configuration revealed very low hysteresis, which is essential for the long-term stability and reproducibility of PSCs. The MOX/Spiro bilayer HTL-based devices exhibited higher PCE, better long-term stability, reduced interfacial trap densities, and higher hole extraction rates in comparison to the reference (pristine Spiro-OMeTAD) devices. These findings suggest that incorporating the MOX layer between perovskite and Spiro-OMeTAD layers significantly enhances the PV performance and provides further exploration for commercial use.